Decision support system in choosing tour packages and travel reservations using simple additive weight (SAW) method on Berkat Hemat Wisata - Fauzi H. Simbolon; Maranata Pasaribu; Sariadin Siallagan (Sean Institute, 2024)
Travel activities' growth as an effort to seek balance, harmony, and happiness with the environment has intensified competition in the tourism industry. Therefore, this study employs the Simple Additive Weighting (SAW) method to aid in selecting travel packages and reservations. This method enables the assessment of alternative performances based on specified criteria such as hotel class, package price, number of tours, and tour duration. The SAW process involves normalizing decision matrices and summing matrix multiplications with a weight vector, resulting in alternative rankings from the largest to the smallest. The case study demonstrates that the selection of travel packages is conducted by assigning weights to each criterion, such as hotel class, package price, number of tours, and tour duration. The final results reveal alternative rankings, facilitating decision-makers in choosing travel packages that align with their preferences. By utilizing the SAW method, this decision support system streamlines the assessment and selection of travel packages, enhancing service quality and consumer satisfaction in the tourism industry.